Roles of corporate entrepreneurship and social capital in relationships among environmental, organizational, and informational capability factors and firm performance. - Ziyae, Babak (2011)
This dissertation examines corporate entrepreneurship at the organizational level of analysis. The current study considers several empirical and theoretical gaps, which have arisen in entrepreneurship literature. The exhaustive scan of the extant literature, more than anything else, has shown that there still exists a void in our understanding of the antecedents and outcome of corporate entrepreneurship. The present study fills these gaps by examining the relationship between various factors stimulating corporate entrepreneurship (antecedents of corporate entrepreneurship). It was further argued that corporate entrepreneurship assists in recognizing opportunities, finding of new sources of value, and manage innovation that leads to the greater firm performance (as a consequence of corporate entrepreneurship. This study also focuses on the examination of the mediating effects of corporate entrepreneurship in the relationship between corporate entrepreneurship antecedents (i.e., environmental factors, organizational factors, and informational capability factors) and firm performance. In addition, moderating effect of social capital on the corporate entrepreneurship-firm performance relationship was also investigated. In the present study, a mail survey was used as the method for data collection. In addition, a total of 354 Iranian SMEs of textile industry constituted the sample of the research. The six research objectives and nine research questions of the study were answered by performing appropriate descriptive and inferential statistical analyses. The hypotheses of the study tested using the hierarchical multiple regression, multiple regression analysis following Baron and Kenny’s three-step procedure, and hierarchical moderated regression. The findings of this study revealed that there is a significant positive relationship between (i) overall environmental factors and corporate entrepreneurship (β=.128, p<.05); (ii) overall organizational factors and corporate entrepreneurship (β=.579, p<.05); (iii) overall informational capability factors and corporate entrepreneurship (β=.128, p<.05); and (iv) corporate entrepreneurship and firm performance (β=.784, p<.05). The evidence from this study also suggested that there is a positive significant relationship between individual dimensions of corporate entrepreneurship (i.e., innovativeness, risk-taking. proactiveness, competitive aggressiveness, and autonomy) and firm performance.